Revisiting life with Martin Heidegger - Zgórecki, Przemysław (Filozofia Chrześcijańska, 2023)
The purpose of this article is to trace the essential foundations of the reduction carried out by young Heidegger, whereby the most primordial experience of life emerges from religious experience. The considerations presented below consistently follow the path described above leading back to the thing itself, that is, precisely back to life itself. Hence, we will not be interested here simply in the religious thinking of the young Heidegger, nor in his relation to the problem of God. Instead, we will try to reconstruct his path back towards life itself. This article admittedly focuses on Heidegger’s early philosophical explorations. It seems, however, that Heidegger remains faithful to the very end to the ambitious goals set by the inconspicuous schema for the Kriegsnotsemester lecture of 1919, outlined with youthful enthusiasm for the search for real life. It is hard to resist the impression that the whole long path of his thinking is just such a constant return to life.